(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluates the outcomes of retroperitoneal laparoscopic surgery for upper ureteral stones at Hà Đông General Hospital. Methods: A cross-sectional descriptive study was conducted on 82 patients diagnosed with upper ureteral stones and treated with retroperitoneal laparoscopic surgery for stone removal. Results: The success rate of the surgery was 100%, with 98.8% of patients experiencing no intraoperative complications. Early postoperative outcomes were as follows: good in 93.9% of cases, average in 6.1%, and no poor outcomes. Preoperatively, 100% of the patients had hydronephrosis, which decreased to 11.1% postoperatively. Conclusion: Retroperitoneal laparoscopic surgery is a safe, effective, and minimally invasive treatment method for ureteral stones.